Digitalization, Platform Dependence, and the Restructuring of Marketing Power in Small Enterprises - Syamsul Bahri; Fatmah Bagis (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objective: Marketing digitalization is increasingly viewed as a key strategy for strengthening the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). However, empirical evidence on how digitalization affects the marketing power of MSMEs still shows mixed results and often assumes a direct impact. This study aims to explain how marketing digitalization shapes MSME marketing power through a gradual mechanism involving dependence on digital platforms and the loss of pricing autonomy.Methodology: This study examines the impact of digitalization intensity on marketing power among MSMEs, with platform dependence as a mediating variable. Using a quantitative approach, data were collected from 210 MSMEs in Kupang. The analysis was conducted using Partial Least Squares StructuralFinding: The results show that digitalization intensity has a significant direct effect on marketing power (β = 0.431, p < 0.001). In addition, digitalization intensity significantly increases platform dependence, which in turn weakens pricing autonomy and affects marketing power. The mediation analysis indicates partial mediation, suggesting that digitalization influences marketing power both directly and indirectly through platform dependence.Conclusion: These findings highlight the dual role of digitalization as both an empowering and constraining force for MSMEs. This study contributes to the integration of Platform Economy Theory and Value Capture Theory by explaining how platform dependence can limit MSMEs’ ability to capture value. Practical implications are discussed for MSME actors and policymakers in managing digital platform engagement.